Illusion of agency in patients with Gilles de la Tourette Syndrome. (April 2016) - Delorme, Cécile; Salvador, Alexandre; Voon, Valerie; Roze, Emmanuel; Vidailhet, Marie; Hartmann, Andreas; Worbe, Yulia
Abstract: The sense of agency refers to the conscious experience of authorship and control over actions. The voluntary or involuntary nature of tics, which are the hallmark of Gilles de la Tourette Syndrome (GTS), is unclear. Here, we studied metacognitive processing of agency in an explicit agency task on non-medicated and medicated GTS patients compared to matched controls. In this task, the participants made judgements of control and performance after completion of a computerized game where they had to catch targets with a cursor by moving the computer mouse. The task included several conditions, where the objective control over the cursor could be normal, disrupted or artificially enhanced. We show that GTS patients, independently of medication status, based their judgments of agency predominantly on the matching between their intention and the outcome, i.e., had an illusion of agency in the task condition where their performance was artificially enhanced. Nevertheless, they recognized not to be fully in control in conditions of disrupted control. The propensity to illusions of agency was negatively correlated with global disease severity. Our findings suggest alterations of metacognition of agency in GTS patients. This illusion of agency could reflect a compensatory mechanism related to tic control, but is more likely to be related to deviant brain maturation in GTS.